Clinical evaluation of dengue and identification of risk factors for severe disease: protocol for a multicentre study in 8 countries - Jänisch, Thomas; Beck, Dorothea; Wirths, Marius; Rosenberger, Kerstin (BMC infectious diseases, 2016)
The burden of dengue continues to increase globally, with an estimated 100 million clinically apparent infections occurring each year. Although most dengue infections are asymptomatic, patients can present with a wide spectrum of clinical symptoms ranging from mild febrile illness through to severe manifestations of bleeding, organ impairment, and hypovolaemic shock due to a systemic vascular leak syndrome. Clinical diagnosis of dengue and identification of which patients are likely to develop severe disease remain challenging. This study aims to improve diagnosis and clinical management through approaches designed a) to differentiate between dengue and other common febrile illness within 72 h of fever onset, and b) among patients with dengue to identify markers that are predictive of the likelihood of evolving to a more severe disease course.
Gesehen am 21.02.2020